Class Conflict and Economic Power in Veronica Roth's Divergent: A Marxist Analysis of Factional Divisions (LITPAM, 2024)
This research is an analysis of the novel Divergent by Veronica Roth. Overall, Divergent tells about the situation of Chicago in the future, which has five factions that support their lives in the city. In this novel there is a conflict between the upper class (Erudite, Dauntless) and the lower class (Abnegation) which is presented by the character Beatrice as the main character who is also a character in the Abnegation faction. The purpose of writing this research is to analyze the existing class differences depicted as factions and the factors used by these factions in taking over power. To achieve this goal, this research uses Marxism theory but only focuses on economic power, class conflict, and factors of conflict. This analysis uses a qualitative descriptive method. The results of this analysis use a Marxism perspective which shows that factional divisions are caused by Economic and Political factors.